Modelling And Characterization Of Stone Wool Fibre Reinforced High Density Polyethylene Composites - Leong, Shu Teng (2016)
Composites are a combination of two or more constituent materials that consist of phases like reinforcement and matrix phase. Polymer matrix composites consist of long or short fibres in a polymer matrix. Most polymer composites have been created to optimize the mechanical properties and are designed to be lighter and stronger to use in variety of applications such as automotive industry, sports equipments, aircraft components and etc.This research investigates the mechanical properties of stone wool (SW) fiber-reinforced high density polyethylene (HDPE) composites at fiber loadings, 0 to 60 wt.% through two methods: experimental and finite element analysis. Nowadays, due to the increase in environmental awareness, the wide spread use of glass, carbon and aramid has greatly decreased due to greater weight, higher cost and adverse environmental impact brought by those fibres. Research into new fibres has significantly increased, making stone wool among the chosen fibres. Stone wool is a natural material that is formed from one earth’s most abundant material. It becomes a mass of fine, intertwined fibres with a typical diameter of 6 to 10 micrometres after an advanced process. SW shows few good characteristics such as a good insulator, lightweight, good quality, sustainable and also environmentally friendly. It also has proven to be a safer option to be used than carbon and glass fibre. The stone wool polymer composites (SWPC) specimens were prepared using the hot compression molding process. These samples were then prepared and tested according to ASTM standards for tensile, flexural and hardness test. Scanning electron microscopy (SEM) was carried out on the fractured surface to observe the interaction between matrix and fiber in the composites. The experimental results revealed that there was an increase in fiber loading which also increases the mechanical properties of the material. Significant improvement of mechanical properties is observed and recorded for 20wt.% SWPC. The results also shows a significant decrease in tensile and flexural properties after 40wt.% SWPC. The hardness test results shows that it improves with the increase of the fibre weight percentage and the value maintained after 40wt.% SWPC. To reveal the actual phenomenon of the composites, finite element modelling and analysis has also been performed. The mechanical properties was predicted using the model developed by ANSYS. The model was then experimentally validated. The model outputs were found to have excellent agreement with the experimental results, with an accuracy of more than 90% for tensile and 85% for flexural test. The accuracy of established ANSYS model proving its robustness and expected to reduce the industrial experimental cost holistically.